2017
DOI: 10.3747/co.24.3182
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Medical Resource Utilization and Costs of Relapsed and Refractory Chronic Lymphocytic Leukemia in Ontario

Abstract: PurposeThe purpose of the present study was to collect medical resource utilization data and costs in Ontario for the management of patients with relapsed or refractory chronic lymphocytic lymphoma (cll) who have undergone at least 1 treatment course and have been stratified by Rai staging.Methods This retrospective longitudinal cohort study, conducted by chart review, analyzed anonymized patient records from two cancer centres in Ontario. Comprehensive records of 86 patients meeting the inclusion criteria wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Of the eight observational studies that reported cost and resource use among patients with R/R CLL, six were conducted in North America (Table 4) [41][42][43][44][45][46][47][48] .…”
Section: Costs Related To Patients With R/r Cllmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the eight observational studies that reported cost and resource use among patients with R/R CLL, six were conducted in North America (Table 4) [41][42][43][44][45][46][47][48] .…”
Section: Costs Related To Patients With R/r Cllmentioning
confidence: 99%
“…HRU data were collected in a retrospective study of medical chart data from 86 patients with R/R CLL (mean age, 65 years; 69% males) undergoing treatment in two facilities in Canada between 2002 and 2012 42 . Of the total population studied, 44.2% (38/86) were receiving fludarabine-based 42 .…”
Section: Costs Related To Patients With R/r Cllmentioning
confidence: 99%
See 2 more Smart Citations